Modifications of fatty acids profile, lipid peroxidation and antioxidant capacity in raw and cooked rabbit burgers added with ginger. (November 2017) - Mancini, Simone; Preziuso, Giovanna; Dal Bosco, Alessandro; Roscini, Valentina; Parisi, Giuliana; Paci, Gisella
Abstract: Effects of ginger powder were evaluated on fatty acid (FA) profile, lipid peroxidation (TBARS) and antioxidant capacity (ABTS, DPPH and FRAP) of rabbit burgers. Burgers were manufactured as control samples (only meat) and two additions of ginger powder (1% and 2%) and stored raw at 4 °C for 7 days. At day 1, 4 and 7 of storage burgers were analysed both as raw and cooked. Ginger powder affected all the tested parameters; both PUFAω3 and PUFAω6 were incremented in raw and cooked samples leading to decreased atherogenicity and thrombogenicity indexes and increased hypo/hypercholesterolemic index and peroxidability index. Lipid peroxidation values of raw and cooked burgers added with ginger were lower than control burgers, at the same time, ABTS, DPPH and FRAP values were incremented by the addition of ginger powder. The results obtained demonstrate the antioxidant capacity of ginger powder as rabbit meat products additive and highlight the capacity of this spice to maintain its characteristics after burgers' cooking. Highlights: Fatty acids profile of burgers added with ginger showed healthiest characteristics. Ginger powder decreased lipid peroxidation of burgers. Antioxidant capacity of burgers was increased by ginger powder. Ginger powder maintained its antioxidant capacity after burgers' cooking.